Dynamics of abundance and biomass of zooplankton in spring-summer season in the Ussuri Bay (Peter the Great Bay, Japan Sea) - Victoria A. Degtyariova (Известия ТИНРО)
Dynamics of abundance and biomass is investigated for zooplankton in shallow and deep-water parts of the Ussuri Bay in May-September of 2007-2011. Boreal copepods prevail in spring and early summer, with domination of wide-spread species Pseudocalanus newmani and Oithona similis (in sum 65-70 % of total number) and neritic species Acartia sp. aff. clausi (28 %), but subtropic copepods Oithona brevicornis and Paracalanus parvus become more abundant in late summer (in sum 50-67 % of total number). Not numerous but large-sized species Sagitta spp., Neocalanus plumchrus , Metridia pacifica , and Calanus glacialis take 30-40 % of the total biomass Two seasonal peaks of zooplankton abundance are observed in the shallow northern part of the Bay (in June and September) but only one seasonal peak (in May) - in its deep-water southern part. Generally, the zooplankton community in the Ussuri Bay is distinguished by high species diversity caused by species with both different zoogeography, as tropical, sub-tropical, boreal, and arctic-boreal ones, and different environmental preference, as residents of brackish, neritic, and oceanic waters (the latter large-sized species provide high biomass of zooplankton). Meroplankton species are presented in the zooplankton community during entire investigated season.